Masjidpreneur: Transformasi Masjid sebagai Pusat Ekonomi Umat dan Inkubator UMKM Berbasis Syariah - fathurrahman, Ayif (MAYARA: Jurnal Pengabdian Masyarakat, 2026)
This community service initiative is based on the suboptimal role of Muhammadiyah mosques as centers of economic empowerment for the ummah, as they are still predominantly focused on ritual functions. Historically, however, mosques have played a strategic role in strengthening the socio-economic fabric of society. In PCM Banguntapan Selatan, the potential of congregants’ micro, small, and medium enterprises (MSMEs) is quite significant, yet it has not been integrated into a mosque-based economic ecosystem. Therefore, the Masjidpreneur program was designed to transform the mosque into a sharia-based center for community economic empowerment. The approach employed is Participatory Action Research (PAR), implemented through stages including needs identification, program formulation, sharia-based entrepreneurship training, MSME mentoring, strengthening mosque economic management, as well as monitoring and evaluation. This approach emphasizes the active participation of both congregants and mosque administrators. The results of the program indicate a transformation in the mosque’s function into a center for economic empowerment, an increase in the entrepreneurial capacity of congregants, the establishment of an embryo of a mosque-based MSME incubator, and the strengthening of more professional and sustainable mosque economic governance. In addition, institutional synergy was fostered among the mosque, Muhammadiyah, and ‘Aisyiyah in building a community-based economic ecosystem. The Masjidpreneur model is effective in promoting the integration of the mosque’s spiritual and economic functions and holds strong potential for replication as a community-based economic empowerment model within the framework of Islamic economics.